2019
DOI: 10.1093/beheco/arz130
|View full text |Cite
|
Sign up to set email alerts
|

Why do females sing?—pair communication and other song functions in eastern bluebirds

Abstract: Female bird song has been underappreciated and understudied, especially in temperate species. Birdsong was originally thought to be a trait used primarily by male songbirds for mate attraction and male/male contest. However, ornithologists have long known that females sing in many tropical songbirds, often for similar functions to male song. Yet, studies of female song in temperate regions remain scarce. Increasing our understanding of the function of female song in temperate species is a powerful step towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…We report that while female song is nearly nine times less frequent than male song, and relegated largely to the first month of the breeding season, it has an overall similar structure to male song and is used similarly in counter-singing, as well as mate-interruption contexts. The use of female song in counter-singing (see supplementary video 1) just prior to clutch initiation is consistent with singing patterns of other Northern temperate breeding species and suggests a functional role for this signal similar to what has been found for female song in those species (Cain et al, 2015; Krieg & Getty, 2016b; Levin, 1996; Rose et al, 2019; Yasukawa, 1989, 1990). Specifically, female barn swallow song could be actively maintained and used by females during this short period of the breeding season when females are establishing and competing for nest sites (Krieg & Getty, 2016b; Rosvall, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…We report that while female song is nearly nine times less frequent than male song, and relegated largely to the first month of the breeding season, it has an overall similar structure to male song and is used similarly in counter-singing, as well as mate-interruption contexts. The use of female song in counter-singing (see supplementary video 1) just prior to clutch initiation is consistent with singing patterns of other Northern temperate breeding species and suggests a functional role for this signal similar to what has been found for female song in those species (Cain et al, 2015; Krieg & Getty, 2016b; Levin, 1996; Rose et al, 2019; Yasukawa, 1989, 1990). Specifically, female barn swallow song could be actively maintained and used by females during this short period of the breeding season when females are establishing and competing for nest sites (Krieg & Getty, 2016b; Rosvall, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…(2018), Rose et al. (2019). All field methods and protocols were approved by the University of Maryland, Baltimore County Institutional Animal Care and Use Committee (IACUC, approval KO01741417).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the field of ornithology has viewed birdsong as a primarily male behavior used for mate attraction and territory defense (Catchpole & Slater, 2008; Rose et al., 2019). However, recent work has demonstrated that female song is both widespread and ancestral in songbirds, and that song may have additional or different functions in females (Odom & Benedict, 2018; Odom et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations